2021
DOI: 10.1007/s10787-021-00850-7
|View full text |Cite
|
Sign up to set email alerts
|

Recent updates on immunological, pharmacological, and alternative approaches to combat COVID-19

Abstract: The pandemic coronavirus disease 2019 (COVID-19) is instigated by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that is mainly transmitted via the inhalation route and characterized by fever, coughing and shortness of breath. COVID-19 affects all age groups with no single cure. The drug discovery, manufacturing, and safety studies require extensive time and sources and, therefore, struggled to match the exponential spread of COVID-19. Yet, various repurposed drugs (antivirals, immune-modulators,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 129 publications
0
6
0
Order By: Relevance
“…Corticosteroids such as dexamethasone and methylprednisolone have been reported to be effective in reducing mortality of patients with severe COVID-19 [ 112 , 113 ]. Also, many study groups have reported that treatment with antivirals, convalescent plasma, biologics targeting IL-1, IL-6, and TNF-α, and other anti-inflammatory drugs has been effective in severe COVID-19 patients to reduce morbidity and clinical severity of the disease [ 114 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Corticosteroids such as dexamethasone and methylprednisolone have been reported to be effective in reducing mortality of patients with severe COVID-19 [ 112 , 113 ]. Also, many study groups have reported that treatment with antivirals, convalescent plasma, biologics targeting IL-1, IL-6, and TNF-α, and other anti-inflammatory drugs has been effective in severe COVID-19 patients to reduce morbidity and clinical severity of the disease [ 114 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Although ring D was generally supposed to be an essential part for the activities of podophyllotoxins, a series of ring D opened deoxypodophyllotoxin (206)(207)(208)(209)(210)(211) showed selective cytotoxicities against the HL-60 cell line (Figure 7) [156]. Oxidization followed by further modification at C-9 led to the synthesis of some carboxylic acid derivatives as esters, amides, nitriles and anhydrides (212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225). Their cytotoxicities were at micromolar range, although less potent than the parent compounds [157].…”
Section: Ring Dmentioning
confidence: 99%
“…Thus, the early detection, treatment, and control of cytokine storms are significant for patients [138]. Interleukin-6 (IL-6) is a cytokine involved in inflammatory and immunological responses [139]. Tocilizumab (TCZ), a humanized monoclonal antibody, is anti-interleukin-6 receptor (IL-6R) and is suggested in critically ill patients with increased IL-6 levels.…”
Section: Immuno-modulatorsmentioning
confidence: 99%